Histopathological Diagnosis of Atopic Eruption of Pregnancy and Polymorphic Eruption of Pregnancy: A Study on 41 Cases - Nunzi, E. (2017)
The specific dermatoses of pregnancy represent a recently reclassified heterogeneous group of pruritic inflammatory skin diseases unique to pregnancy that include pemphigoid gestationis, polymorphic eruption of pregnancy (PEP), intrahepatic cholestasis of pregnancy, and atopic eruption of pregnancy (AEP). Among them, PEP and AEP are the most frequent ones. We performed a histopathological study of a series of PEP and AEP patients (n = 41). Twenty-two patients had PEP that started in the third trimester in 16 (73%) patients and postpartum in 6 (27%) patients. Histopathology revealed a superficial or superficial and deep perivascular dermatitis with eosinophils in all biopsies and signs of a lymphocytic vasculitis in 5 (23%) cases. Epidermal changes, including epidermal hyperplasia, spongiosis, and parakeratosis, occurred in 8 cases, in particular in elder lesions. Nineteen patients had AEP that started earlier [ less than third trimester, 14 (74%) patients; third trimester, 5 (26%) patients]. Clinically, 5 (26%) patients showed eczematous lesions, 7 (37%) papular lesions, 3 (16%) presented both eczematous and prurigo lesions, and 4 (21%) experienced exacerbation of preexisting atopic dermatitis. Histopathologically, AEP was characterized by a perivascular lymphohistiocytic infiltrate with frequent eosinophils (74%) and epidermal changes in all but most of P-type biopsies. No definitive differential histopathological criteria between PEP and AEP were found. Only lymphocytic vasculitis with a mixed infiltrate with eosinophils was more frequent in PEP patients. Timing of onset, morphology of skin lesions, and a detailed clinicopathologic correlation are essential for diagnosis.